A Disaggregate Analysis of Consumer Choice under Uncertainty - Epstein, L. (Econometrica, 1975)
[The standard two-period consumer choice problem, where current consumption must be decided upon subject to uncertainty about future income and prices is considered in this paper. Previous analyses have been limited to an economy where either there is only one commodity or consumer preferences have a restrictive form. The primary objective of this paper is to generalize these analyses so that these limitations are eliminated. This is accomplished by applying the theory of duality.]